Qualitative Scenario Building for Post-carbon Cities - Margaretha Breil; Cristina Cattaneo; Katie Johnson (Fondazione Eni Enrico Mattei (FEEM), 2015)
In defining the transition towards a post-carbon future, understanding the needs and determinants for policy priorities in different types of cities will help tailor a common roadmap that can be adopted under various socio-economic contexts. This paper provides an analysis of results collected in a participatory scenario building exercise undertaken within a research project on post-carbon urban futures (Post-Carbon Cities of Tomorrow, POCACITO). It is based on local workshops organised in nine European case study cities, which employed a three-step methodology consisting of an initial assessment, vision building and backcasting exercises. All exercises had a strong focus on the inclusion of stakeholders. Comparison of outcomes from the visions and scenarios resulting from these workshops provides insights on the drivers that determine different priorities in policy action for cities working to transition toward post-carbon futures. Results from the case study cities show similar elements in the strategies proposed by stakeholders, focusing primarily on urban projects for energy efficiency and the transition to non-fossil energy resources. However, the specific mix of strategies envisaged for each city has been influenced by local issues, such as the geographical location or the size, as well as different points of departure with regards to emission reductions and sustainability strategies already achieved.
Keywords: Q50; Q56; Q58; 330; Post-carbon; Visions; Scenarios; Transition; Sustainability